O-004 Prospective, multi-centered, EMS-administered, PRe-hospital validation study of the rapid arterial occlusion evaluation (RACE) scale for detecting large vessel occlusion stroke in the United States compared to the original RACE validation study from spain: a subanalysis of the PREDICT study. (4th August 2020) - Cruz, A; Fortuny, E; Ugiliweneza, B; Wang, D; White, A; Khattar, N; Adams, S; Gallinore, B; Ding, D; Wolfe, S; Heck, D; James, R
Abstract : Introduction: Pre-hospital identification of patients with large vessel occlusion (LVO) is critical in the timely triage of thrombectomy-eligible LVO patients to comprehensive stroke centers. The Rapid Arterial oCclusion Evaluation (RACE) scale was prospectively validated to identify LVO patients by EMS in Spain and has been widely adopted in the United States, though these healthcare infrastructure and EMS systems may differ significantly and these results may not be completely applicable in the US. This study prospectively validates the RACE scale as administered by US-based EMS personnel in the pre-hospital setting and we compare our results to the originally published results. Methods: 232 adult patients suspected of having a stroke by EMS and transported to a participating comprehensive stroke center had the RACE scale administered prospectively and recorded in a secure web-based database. Admission NIHSS score and final diagnosis were recorded. Cerebrovascular imaging studies (CTA, MRA or DSA) were reviewed by a blinded, independent Neuroradiologist to determine LVO diagnosis. We used SAS and c-statistics to create receiver operating characteristic (ROC) curves to determine the area under the curve (AUC) and optimal cut point (CP) scores for the RACE scale. We also calculated the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), overall accuracy for the optimal CP score. Results: Our analysis of the predictive capability of the RACE scale showed similar predictive capacities for radiographically-confirmed LVO in patients prospectively tested in the US as compared to the original Spanish RACE scale population. The best CP score value predictive of LVO in our US-RACE study was determined to be ≥6, compared to the original Spanish study which was ≥5 (table 1 ). The overall prevalence of LVO as defined in our study was 13.4%, compared to a prevalence of 21.3% for the original paper's definition of LVO. Conclusion: This is the first prospective validation of the RACE scale performed in the US. These results demonstrate that the RACE scale retains the previously published predictive value in both the US and Spain in accurately identifying LVO stroke in a prehospital setting by EMS. Disclosures: A. Cruz: None. E. Fortuny: None. B. Ugiliweneza: None. D. Wang: None. A. White: None. N. Khattar: None. S. Adams: None. B. Gallinore: None. D. Ding: None. S. Wolfe: None. D. Heck: None. R. James: None.